Age-related change in muscle strength, muscle mass, and fat mass between the dominant and non-dominant upper limbs - Pang, Jing; Tu, Fuyi; Han, Yiwen; Zhang, Enyi; Zhang, Yan; Zhang, Tiemei (Frontiers in Public Health, 2023)
Background Any form of physical activity is recommended for the older adults to maintain their physical function; however, the effect of daily activities on muscle function still needs to be investigated. Humans always use one dominant hand to perform tasks, providing a natural situation for research on the effect of daily activities on muscle function. Methods Five hundred and twenty-six healthy adults were recruited from the community in Beijing. Muscle strength was assessed using a handgrip dynamometer, lean mass, fat mass, bone area and bone mineral content of upper limbs were assessed using dual-energy X ray-absorptiometry. The results were compared between the dominant and non-dominant upper limbs. Results The dominant upper limb had better muscle strength, lean mass, bone area and bone mineral content than the non-dominant side. The difference in muscle strength and lean mass between the two upper limbs decreased with the advanced age. In older age, fat mass of upper limbs increased in men, but not in women. Conclusion Daily activities can maintain better muscle function in the dominant upper limb than in the non-dominant side; however, the delaying effect on age-related decline in muscle function was limited.